Living with water: An Ethnographic Study Relating to Water and Infrastructure Entanglements, in the Hout Bay Suburb of Cape Town, for a Water Sensitive Designed "Liveable" Neighbourhood - Gara, Faith (Social Anthropology, 2022)
Inclusive water management implies considering the diverse relationships different people have with water, other values that people assign to water, and the ecological impacts of employed strategies. Faced with increasing water scarcity and environmental degradation, it has become critical that we look for alternative ways of managing essential natural resources, including using different approaches to resource management. Water management is mainly dominated by technical and natural scientists, with designs motivated by water supply costs and benefits. This neglects to consider other dimensions associated with water use and access, such as social, cultural and histories that inform how people are situated at different resource allocation intervals. Moreover, how we relate to water affects our environment, from soils, plants and other non-human species, and this, in turn, affects our wellbeing as all the processes that are entangled with life making. For these reasons, social scientists must take part in all water management processes to bring forth other neglected aspects of people's relationship with water and ecologies that are usually overlooked by hard sciences. My research forms part of the Liveable Neighbourhood project, which seeks to redesign the existing neighbourhood of Hangberg in Hout Bay using a Water Sensitive Design. Thus, my study's role is to provide ethnographic data to a field dominated by bureaucratic structures, engineers; urban planners; urban designers and architects; to add the ways of knowing and understand better the diverse relations various communities in Hout Bay have with water. This is essential to enable the formulation of Water Sensitive Designs (WSDs) that include residents' inputs in what they consider 'liveable'. Most interventions that do not consider context-specific needs and dynamics often fail to have relevance and end up unsustainable.